Mechanical Properties of WC-Co Alloys with Various Mixing and Milling Conditions using High Energy Ball Miller - Song, Joon-Woo; Md. Raihanuzzaman, Rumman; Hong, Soon-Jik (Current Nanoscience, 2014)
This study aims to understand the changes in mechanical properties when WC-7.5wt%Co and WC-12wt%Co compositions were experimented with various mixing, milling and consolidation conditions. Magnetic Pulsed Compaction (MPC) was used to consolidate WC-7.5wt% Co and WC-12wt% Co powders where high-energy ball milling with varying duration was employed for generating various powder types. Mechanically alloyed milled, non milled and mixed (non milled and milled powders in certain proportions) powders with compositions of WC-7.5wt% Co and WC-12wt% Co were used, followed by applying high pressures to form the bulks. Maximum densities for mixed milled and non milled WC-Co bulks after MPC were found to be around 60-65%, which later turned nearly 82% after sintering, while a maximum hardness of over 1400 Hv was observed in WC-12wt%Co sample. Density, hardness and other microstructural behavior did not illustrate substantial changes when mixed powders were used, although variations were noticed when non-milled powders were used for consolidation.
Keywords: sintering